P234 A RARE CASE OF ACUTE RIGHT HEART FAILURE PRESENTED IN A CASE REPORT. (18th May 2022) - Avondo, S; Zaccaro, L; Albani, S; Pelloni, E; Bonino, C; Biava, L; Scacciatella, P
Abstract: Case Summary: A 62–year–old male with multiple cardiovascular risk factors, presented at the ED with signs and symptoms of right heart failure, Doppler echocardiography showed a severe dilatation and dysfunction of the right ventricle and left ventricular diastolic dysfunction. After initial stabilization with diuretics and inotropes, the patient performed a coronary angiogram with evidence of severe multivessel coronary artery disease and combined pre–capillary and post–capillary pulmonary hypertension as shown by the right heart catheterization. After complete revascularization, the diastolic function of the left ventricle improved dramatically, and the right ventricle recovered completely. Discussion: We presented a paradigmatical case of acute right heart failure secondary to left ventricular diastolic impairment in a patient affected by severe ischemic coronary artery disease. Several risk factors are associated with RVD in HFpEF: atrial fibrillation, male sex, chronic obstructive pulmonary disease. Diastolic performance of the LV is one of the main determinants of the right ventricular function, which, in turn, is proven to have prognostic implication in HFpEF. Nowadays, there is no evidence–based treatment for right heart failure secondary to decompensated HFpEF and therapy should be tailored to the individual patient's response.